Il progetto repubblicano di Giuseppe Mazzini e l’Inghilterra: dalla democrazia etica alla democrazia sociale, 1845-50 - Marco Barducci (Laboratoire Italien)
Over at least the last fifteen years, one of the founding fathers of Italian unity Giuseppe Mazzini (1805-1872) has acquired the status of European democratic and republican thinker. Most part of scholarship on Mazzini’s democratic republicanism has pointed out the centrality of the ethical-religious dimension of his political project. This essay argues that from the publication of his Thoughts upon democracy in Europe (1846-1847) to the Mazzini’s Manifesto (1850), the languages used by Mazzini assumed a more distinctively social meaning although never a socialist one. Whereas its intellectual origins dated back to the period of Mazzini’s exile in France – when he was fascinated by the political ideas of Buonarroti, Lamennais, Leroux and Saint-Simon – it was especially during the many years spent in England (1837-48, 1851, 1857, 1860) that the republican and democratic lexicon of the exile, in which a particular relevance assumed words like “association”, “people” and “nation”, acquired a distinctly social meaning.